Exploring non-linear relationships between neighbourhood walkability and health: a cross-sectional study among US primary care patients with chronic conditions. Issue 8 (19th August 2022) - Bonnell, Levi Nicolas; Troy, Austin R; Littenberg, Benjamin
Abstract : Background: A recent study of licensed drivers found a non-linear relationship between density of non-residential destinations (NRDs), a proxy for walkability and body mass index (BMI) across a wide range of development patterns. It is unclear if this relationship can be replicated in a population with multiple chronic conditions or translated to health outcomes other than BMI. Methods: We obtained health data and home addresses for 2405 adults with multiple chronic conditions from 44 primary care clinics across 13 states using the Integrating Behavioral health and Primary Care Trial. In this cross-sectional study, the relationships between density of NRDs (from a commercial database) within 1 km of the home address and self-reported BMI, and mental and physical health indices were assessed using several non-linear methods, including restricted cubic splines, LOWESS smoothing curves, non-parametric regression with a spline basis and piecewise linear regression. Results: All methods demonstrated similar non-linear relationships. Piecewise linear regression was selected for ease of interpretation. BMI had a positive marginal rate of change below the NRD density inflection point of 15 establishments/hectare (β=+0.09 kg/m 2 /non-residential buildings ha-1; 95% CI +0.01 to +0.14), and a negative marginal rate of change above the inflection point (β=−0.02; 95% CI −0.06 to 0.02). Mental health decreased with NRD density below the inflection point (β=−0.24; 95% CI −0.31 to −0.17) and increased above it (β=+0.03; 95% CI −0.00 to +0.07). Results were similar for physical health (β= −0.28; 95% CI −0.35 to −0.20) and (β=+0.06; 95% CI 0.01 to +0.10). Conclusion: Health indicators were the lowest in middle density (typically suburban) areas and got progressively better moving in either direction from the peak. NRDs may affect health differently depending on home-address NRD density. Trial registration number: NCT02868983 .